Characterization of Key Odorants During Processing of Minty-like Aroma ‘Rucheng Baimaocha’ Black Tea - Jian Ouyang; Ronggang Jiang; Qi Liu; Hongyu Chen; Xiaoqin Yi; Yuzi Yang; Fangfang Huang; Juan Li; Haitao Wen; Ligui Xiong; Jianan Huang; Zhonghua Liu (Foods)
The characteristic minty-like aroma of ‘Rucheng Baimaocha’ black tea (RCBT) enhances the tea’s unique flavor profile, driving high demand among consumers. The dynamic changes in key aroma compounds in minty-like RCBT were elucidated by sensory evaluation and gas chromatography olfactometry quadrupole time of flight mass spectrometry (GC × GC-O-Q-TOF-MS). The results indicated that during processing, the aroma of RCBT transitions from a fresh to floral, sweet, and minty-like aroma. Among the 189 identified volatile compounds, alcohols constitute the predominant category (over 50%), with 71 compounds identified as key differential compounds across all stages. Aroma analysis revealed that 28 compounds with odor activity values (OAV) > 1 were the primary contributors during RCBT processing. Notably, minty-like odorants in RCBT were primarily derived from the metabolic pathways of the methylerythritol phosphate (MEP) and mevalonic acid (MVA), lipid oxidation, and phenylalanine. These findings offer theoretical insights for improving unique black tea quality and optimizing processing techniques.